Choice of Antimicrobials in Surgical Prophylaxis - Overuse and Surgical Site Infection Outcomes from a Tertiary-Level Care Hospital - Vippadapu, Prasanna; Gillani, Syed Wasif; Thomas, Dixon; Ahmed, Fiaz; Gulam, Shabaz Mohiuddin; Mahmood, Rana Kamran; Menon, Vineetha; Abdi, Semira; Rathore, Hassaan Anwer (Frontiers in Pharmacology, 2022)
Background: This study was aimed to describe the choice of Surgical Antibiotic Prophylaxis at a tertiary-level care hospital in Ajman, United Arab Emirates. It also associated the choice between two leading antimicrobials for the SAP to the site of surgery. Methods: A descriptive drug use evaluation was performed retrospectively to study choices of antimicrobials in surgical antibiotic prophylaxis. An analytical cross-sectional study design was used to develop a hypothesis regarding the choice of ceftriaxone. Data were collected from the medical records of Thumbay University Hospital from July 2020 to December 2020. Results were presented in numbers and percentages. Results: SAP data were collected from 199 patients, of which 159 were clean or clean-contaminated. Dirty surgeries (18) needed a higher level of antimicrobials as there were infections to be treated. For other surgeries with no infection, misuse of antimicrobials was found regarding the choice of antimicrobials. Surgical antibiotic Prophylaxis was administered within the recommended time prior to surgeries. Ceftriaxone was preferred over cefuroxime in all types of surgeries based on the timing of Surgical Antibiotic Prophylaxis, wound classification, and the surgical site. A statistically significant association for choice of ceftriaxone over cefuroxime was found regarding surgical sites (p-value <0.05).About 99% of the patients were prescribed discharge antimicrobials when 158 (80%) surgeries were clean or clean-contaminated. Conclusion: Misuse of antimicrobials was found in surgical antimicrobial prophylaxis Ceftriaxone was preferred more than cefuroxime in all types of surgeries.